О разрешимых группах, все собственные фактор-группы которых имеют конечный ранг - Тушев, А.В. (Український математичний журнал, 1993)
Вивчаються скінченнопороджені фінітно-апроксимовні розв’язні групи нескінченного спеціального рангу, всі власні нормальні підгрупи яких визначають фактор-групи скінченного спеціального рангу. This paper deals with finitely generated finitely approximable solvable groups of infinite special rank, all proper normal subgroups of which determine the factor groups of finite special ranks.